26. RESEARCHING ON THE CLINICAL TREATMENT EFFECT OF HSN LIQUID EXTRACT IN ALCOHOLIC LIVER DISEASE (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effects on clinical and paraclinical indices of HSN liquid extract in the treatment of alcoholic liver disease. To evaluate the adverse effects of the method.Methods: Interventional research, clinical trial, pre-post treatment comparison on 30 patients diagnosed with Alcoholic Liver Disease, treated at the Traditional Medicine Hospital of the Ministry of Public SecurityResults: After 7 days, the clinical symptoms of the patients all improved, in which the symptoms of fatigue decreased from 100% to 70%, anorexia decreased from 80% to 50%, fever from 26.7 to 3.3%, with p < 0.05. After 15 days and 30 days of treatment, the clinical symptoms of the patients all improved significantly, with statistical significance with p < 0.05. The rate of patients with withdrawal syndrome tended to decrease, the difference was not statistically significant with p > 0.05. The rate of patients with symptoms of flank pain, poor appetite, nausea, vomiting, jaundice and fever according to TCM improved statistically with p < 0.05. After 30 days of treatment, no patients were recorded to have unwanted clinical effects. The number of red blood cells, white blood cells, platelets, MCV values, urea, and creatinine did not change statistically with p > 0.05.Conclusion: HSN liquid extract is highly safe and effective in treating alcoholic liver disease, demonstrated in both clinical and paraclinical indices.
Keywords: alcoholic liver disease; HSN; traditional medicine